Study on electrical and physical properties of PEMA/PVC blend based polymer electrolytes for its application in proton electrochemical cell / Shahrul Amir - Amir, Shahrul (2011)
In this work, PEMA was used as the principle host to prepare PEMA/PVC blend, PEMA/PVC-NH4I electrolyte and PEMA/PVC-NH4I-EC plasticized electrolyte systems using solution casting technique. The prepared samples were characterized using XRD, DSC, FTIR, and IS in order to investigate their structural, thermal and electrical properties. XRD and DSC show that the degree of amorphousity of PEMA increases with increasing concentration of PVC. The interactions between the polymers are indicated by FTIR studies and are believed to occur between carbonyl group and chlorine. The polymer blend with PEMA:PVC of ratio 70:30 yielded the most amorphous film. This blend system was selected for the preparation of polymer electrolytes with NH4I as the dopant. Impedance study showed that the conductivity of the blend based electrolyte system increases with increasing NH4I concentration. The system containing 40 wt % of salt exhibited optimum room temperature conductivity of 4.44 x 10"5 Scm'1 . The increase of conductivity is attributable to the increase in the number of ions as the salt concentration is increased. The increase in conductivity is also attributable to the increase in amorphousity in the electrolytes as shown by XRD and DSC studies. The interactions between the polymers and salt were confirmed by FTIR studies where interactions occurred between NH4+ with PEMA and PVC. In order to further improve the conductivity of the optimum salted system, EC plasticizer was added. XRD and DSC studies showed that the amorphousity of the salted system increased with addition of EC while impedance study showed an enhancement of conductivity. The system containing 40 wt % EC exhibited the highest room temperature conductivity of 1.42 x 10"4 Scm"1 . The interactions between polymer, salt and plasticizer were confirmed by FTIR studies. Temperature dependent conductivity studies showed that conductivity increased with the reciprocal of temperature. The plasticized PEMA/PVC-NH4I-EC system with the highest conductivity was used to fabricate all-solid-state proton electrochemical cells. The electrochemical cell discharged at high load or low current drain had the longest time of stable performance. This indicated that the polymer electrolyte was more suitable for low current density battery applications.